KAUM SANTRI MOJOKUTO DAN KAUM SANTRI FRONT PEMBELA ISLAM (Studi Tentang Oposisi Biner: Kolot dan Modernis dalam Konsepsi Cliffor Geertz) - . Mustari (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Research on the influence of Arabic syntax to Malay language orIndonesia language in 19th century is really difficult to be found. In fact, the 19th century is the century that is important in the assessment phase of the Indonesia grammar (Malay), because in this phase began many grammar books and dictionaries of Malay language, both written by Europeans (British-Dutch- French), as Marsden (1812), Crawfurd (1852), Favre (1875), Hollander (1882), and Wijk (1889), as well as written by the Malay people Raja Ali Haji (1850 and 1859).There are fundamental differences between the grammar books written by the Dutch and the Malays. Books written by Europeans was Europe-centric, while the book written by the Malays are very Arab-centric. In fact, since Islam arrived in the archipelago, the influences of Arabic syntax are felt in the archipelago texts, especially religious texts. The fact that the Arabic influence is strong enough to precisely the Malay language syntax encourage Ronkel (1899) wrote an article entitled